Nilai–Nilai Profil Pelajar Pancasila Dalam Cerita Rakyat Legenda Sungai Tapung Rokan Hulu - Sari, Ira Gustiana; Ningsih, Rika (UIR Press, 2026)
The globalization era demands that Indonesia's younger generation possess strong character rooted in national values, in addition to academic intelligence. In response, the Merdeka Curriculum emphasizes strengthening the Pancasila Student Profile, which requires a contextual learning approach. Folklore, as one form of local wisdom, is considered a potential medium for effective character education. This study aims to identify and analyze the values of the Pancasila Student Profile in the folktale Legenda Sungai Tapung from Rokan Hulu. This research employs a qualitative approach using content analysis method. Data were collected through non-participant observation, documentation of the book Legenda Sungai Tapung, Kumpulan Cerita Rakyat Rokan Hulu, and field notes. Data analysis techniques were carried out through unitizing, category development, coding, frequency counting, and interpretation. The results show that all six dimensions of the Pancasila Student Profile are represented in the legend. The dimension of faith, devotion to God Almighty, and noble character is the most dominant (found in 7 quotations), followed by the dimension of cooperation (5 quotations), independence (3 quotations), critical reasoning and creativity (2 quotations each), and global diversity (1 quotation). This research concludes that Legenda Sungai Tapung not only serves as cultural preservation but is also a rich source of values for strengthening character education in accordance with the Pancasila Student Profile in the implementation of the Merdeka Curriculum.